2017
DOI: 10.1021/acs.jctc.6b01143
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Walking of Zerovalent Nickel on Aryl Halides

Abstract: While ring-walking is a critical step in transition metal catalyzed cross-coupling reactions, the associated metastable intermediates are often difficult to isolate and characterize. In this work, theoretical structures and energetics for ring-walking and oxidative addition of zerovalent nickel with 1-bromo-2-methylbenzene, 2-bromopyridine, 2-bromo-3-methyl-thiophene, and 2-bromopyrrole were computed at the B3LYP-D3/TZ2P-LANL2TZ(f)-LANL08d level. The mechanisms vary qualitatively with substrate ring size and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Ring-walking of Ni(dppp) and the corresponding oxidative addition of 1-bromo-2-methylbenzene (solid red, X = C–CH 3 ) and 2-bromopyridine (dashed blue, X = N); energies are given relative to the separated catalyst and substrate and were computed at the B3LYP-D3/TZ2P&LANL2TZ-(f)&LANL08d level of theory. Adapted from ref (635). Copyright 2017 American Chemical Society.…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…Ring-walking of Ni(dppp) and the corresponding oxidative addition of 1-bromo-2-methylbenzene (solid red, X = C–CH 3 ) and 2-bromopyridine (dashed blue, X = N); energies are given relative to the separated catalyst and substrate and were computed at the B3LYP-D3/TZ2P&LANL2TZ-(f)&LANL08d level of theory. Adapted from ref (635). Copyright 2017 American Chemical Society.…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…Further calculations were undertaken to model the ringwalking [38][39][40][41][42] step, using 2a-Br and 3-Br as substrates. In each case, three h 2 -complexes are linked by two transition states, leading from the carbonyl group to the halide site ( Fig.…”
Section: Computational Modelling Of Ring Walking and Oxidative Additionmentioning
confidence: 99%
“…We have shown that aryl aldehydes and ketones can displace ligands such as COD from a Ni 0 center. The resulting selectivity is likely due to a subsequent 'ring-walking' process, [31][32][33][34][35] as selectivity is only obtained when the aryl halide site is in conjugation with the aldehyde or ketone. This coordination behavior results in selectivity in catalytic cross-coupling reactions, to the extent that the normal order of reactivity of aryl halides (I > Br > Cl) is changed substantially.…”
Section: Discussionmentioning
confidence: 99%